Short-term coastal landscape evolution in Cirebon bay using coastline environment analysis - Pratama, Raden Yudi; Sulaksana, Nana; Sukiyah, Emi; Iskandarsyah, Teuku Yan Waliana Muda; Novico, Franto; Zulfahmi, Zulfahmi; Sudjono, Evi Hadrijati; Ranawijaya, Duddy (Journal of Environmental Engineering and Landscape Management, 2023)
The landscape of Java’s north coast is dominated by a mild slope covered by soft sediment, which faces many environmental issues. These issues have been identified, and the simple technique of overlaying Landsat imagery shows the evolution of the landscape along the coast. Survey campaigns in 2006 and 2018 verified the Landsat overlay, and the 210Pb dating analysis aids in describing the sedimentation rate along the coast. The results demonstrate that accretion evolution dominates exclusively in Cirebon’s coastline landscape, with coastal gains reaching 1463.88 ha over four decades and the sediment rate from 1977–1997 estimated at 0.27–0.33 cm/year. Compared to the earlier decade, the recent two periods from 1998 to 2018 demonstrate a more extensive desire for progressive accretion affected by the longshore sediment transport. Hence, special attention should be paid to the northern coast of Java to estimate the sedimentation rate and the advanced coast.